2017
DOI: 10.4236/ojgen.2017.71006
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate Reductase (MTHFR) Gene Mutations in Patients with Idiopathic Scoliosis: A Clinical Chart Review

Abstract: The effects of genetic variations of methylenetetrahydrofolate reductase (MTHFR) enzyme activity have been the discussion of many research papers. It has been associated with multiple neurological sequelae, and has been implicated in other chronic diseases. Although many genetic influences on the development and/or progression of idiopathic scoliosis have been reported, there has been no report of any relationship between MTHFR mutations and idiopathic scoliosis. This paper compared two groups of patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…showed that patients with idiopathic scoliosis had a higher rate of methylenetetrahydrofolate reductase (MTHFR) polymorphism of the A1298C allele compared with non-scoliotic controls [10]. Another enzyme in the methylation cycle, catechol-O-methyl transferase (COMT) degrades catecholamine neurotransmitters (dopamine, norepinephrine, and epinephrine) into their constituent metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…showed that patients with idiopathic scoliosis had a higher rate of methylenetetrahydrofolate reductase (MTHFR) polymorphism of the A1298C allele compared with non-scoliotic controls [10]. Another enzyme in the methylation cycle, catechol-O-methyl transferase (COMT) degrades catecholamine neurotransmitters (dopamine, norepinephrine, and epinephrine) into their constituent metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Несмотря на то что гены ферментов фолатного цикла не исследовали у больных с идиопатическим сколиозом, эти гены отвечают за активность ферментов реакций метилирования, которые от-ветственны за многие ферментные превращения, включая обмен мелатонина. Учитывая тот факт, что дефицит и аномалии сигнальной системы мелатонина служат одним из этиологических факторов идиопатического сколиоза [12,13], изменения в генах, отвечающих за кодирование в активности ферментов фолатного цикла, например МТНFR, могут быть связаны с идиопатическим сколиозом [14].…”
Section: Introductionunclassified